134PIdentification, development and validation of a circulating miRNA-based diagnostic signature for early detection of gastric cancer. (24th November 2019) - Izumi, D; Gao, F; Chen, Y; Ishimoto, T; Horino, K; Shimada, S; Kodera, Y; Baba, H; Chen, J; Wang, X; Goel, A
Abstract: Background: Although endoscopic surveillance remains the gold standard for diagnosing asymptomatic gastric cancer (GC) patients, associated costs and its invasive nature render it inadequate as a screening approach. Development of less invasive tests is needed for surveillance of early stage GCs. Over the last decade, tumor-derived miRNAs in peripheral blood are emerging as promising disease biomarkers. Herein we have conducted a comprehensive miRNA expression profiling, followed by bioinformatic analysis to establish a novel serum-based miRNA signature for the diagnosis of patients with GC. Methods: We analyzed tissue miRNA expression profiles in three patient cohorts (n = 602) in an in-silico discovery step, during which the robustness of candidate biomarkers was tested and validated. The performance of this miRNA signature was evaluated in a serum training cohort (n = 327). Using a logistic regression model, the panel was further refined, and this circulating miRNA signature was validated in two prospective cohorts (n = 174, 175). Results: Genome-wide analysis of miRNA expression data resulted in identification of 10-miRNAs that distinguished cancer tissues from normal mucosa in three independent datasets (AUC = 0.984, 0.939 and 1.000). Using a serum training cohort, the miRNA candidates were further refined to six-circulating-miRNA signature. This miRNA signature demonstrated a robust diagnostic value in the training cohort. Subsequently we demonstrated robustness of the signature in two prospective cohorts (AUC = 0.87, 0.86). Remarkably, the 6-circulating-miRNA signature was able to detect early stage GC patients robustly (AUC = 0.855). Furthermore, the signature was significantly superior at identifying patients with GC to conventional tumor markers, CEA (P = 0.0001) and CA19-9 (P = 0.0001). Conclusions: Using a comprehensive data analysis followed by substantial clinical validations, involving over 1600 GC tissue and serum specimens across 7 independent cohorts, we developed a novel 6-circulating-miRNA signature, which demonstrated an unprecedented diagnostic value and a great promise for early non-invasive detection of GC. Legal entity responsible for the study: Daisuke Izumi. Funding: NIH. Disclosure: All authors have declared no conflicts of interest.